Rehabilitación de un bien patrimonial como espacio de inclusión en el centro histórico de Ibarra - Chiliquinga Chiran, Edwin Armando (2023)
The end-of-career work consists in the rehabilitation of a heritage asset as an inclusion space in the historic center of Ibarra. The base building dates from 1910, which has allowed it to be part of the historic center of the city, and be inventoried by the National Institute of Cultural Heritage - Ecuador\; It is locat-ed in block number 13 corresponding to the cadastral map of the historic center of the city of Ibarra. Its limits are north Pedro Moncayo Street, south Juan de Velasco Street east Juan Montalvo Street and west Juan de Salinas Street. Currently, the old town does not have inclusive and sustainable spaces. Therefore, the project is about an inclusion center suitable for all audiences where society’s awareness and care for people with disabilities is achieved. In addition, the project aims to regenerate public space with the connection of two important land-marks of the city, (the Obelisk, Gonzales Suarez and Francisco Calderón), through the pedestrianization of Juan de Velasco Street. For this, the urban network theory, the characteristics and needs of people with disabilities, both at the macro and micro level of the environment, were taken as a reference. If you are looking for an inclusive and sustainable pubic space, which is focused on guaranteeing accessibility and mobility for those with a degree of disability. For all this, important aspects such as their location, close relationship and influence between these architectural elements were taken into account\; It seeks to have a complementary operation, where different types of disabilities are managed, so it will require a modulation, which allows to provide a solution to the mobility and accessibility of these people.